Impact of acute geriatric care in elderly patients according to the Screening Tool of Older Persons' Prescriptions/Screening Tool to Alert doctors to Right Treatment criteria in northern France. Issue 2 (21st March 2015) - Frély, Anne; Chazard, Emmanuel; Pansu, Aymeric; Beuscart, Jean‐Baptiste; Puisieux, François
Abstract : Introduction: In France, over 20% of hospitalizations of elderly people are a result of adverse drug events, of which 50% are considered preventable. Tools have been developed to detect inappropriate prescriptions. The Screening Tool of Older Persons' Prescriptions/Screening Tool to Alert doctors to Right Treatment (STOPP/START) criteria are innovative and adapted to French prescriptions. This is one of the first French prospective studies to evaluate the impact of acute geriatric care on prescriptions at discharge in elderly patients using the STOPP/START criteria. Method: The evaluation of prescriptions according to STOPP/START was carried out on admission and at discharge of patients in acute geriatric units at three hospitals in the Nord‐Pas de Calais region, France. A total of 202 elderly hospitalized patients were included during the 4.5 months of the study (1.5 months per center). Results: The mean number of drugs was seven on admission and at discharge. Over half of the prescriptions at admission contained at least one potentially inappropriate medication or one potential prescription omission. The prescriptions at discharge contained significantly fewer potentially inappropriate medications than prescriptions on admission ( P < 0.001). In contrast, there was no difference between prescriptions at discharge in terms of potential prescription omissions. Conclusion: Acute geriatric hospitalization in France improves prescriptions in terms of potentially inappropriate medication, but has no impact on potential prescription omissions. Further studies must be carried out to see if STOPP/START could be used as a tool in French prescription.Geriatr Gerontol Int 2016; 16: 272–278.